A lattice model for ferroelectric superlattices - Chew, Khian Hooi; Shin, F.G.; Ishibashi, Y. (2006)
A one-dimensional lattice model based on the Landau-Ginzburg theory to study the intrinsic properties of a periodic superlattice with interfacial coupling is developed. The effects of thickness and interfacial coupling on the properties of a superlattice consisting of alternating ferroelectric and paraelectric constituent layers are investigated. Competition between the thickness effects of each constituent layer is expected and indeed can play an important role in governing the properties of an interface-coupled superlattice, depending on the strength of the interfacial coupling. This work may provide useful information on the possibility of manipulating structures to obtain the desired properties for specific applications.